2011
DOI: 10.1111/j.1447-0756.2011.01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth following severe symmetric fetal growth restriction due to reactivation of Epstein–Barr virus infection in pregnancy

Abstract: Epstein-Barr virus (EBV) infection in pregnancy and consequent fetal outcomes are rarely reported. The majority of cases described strongly support the possibility of transmission of this virus in utero and during delivery, resulting in stillbirth and/or congenital defects. We present a case of EBV reactivation in pregnancy that caused a severe symmetrical fetal growth restriction (FGR) and ultimately spontaneous fetal death. A 36-year-old woman, whose infection status was undetermined, was diagnosed with seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Haeri et al who investigated the prevalence of EBV seropositivity in 64 healthy pregnant women [ 36 ], demonstrated that 22 (35%) women showed EBV reactivation during pregnancy, regardless of maternal age, race, parity, or insurance type [ 36 ]. Moreover, previous reports have clarified that EBV reactivation during pregnancy lead to poor obstetrical outcomes, such as fetal growth restriction [ 37 ], shorter pregnancy duration [ 38 ], and lower birth weight [ 38 ], despite not showing any symptoms. Thus, we recommend transabdominal ultrasound and/or nonstress tests to determine the presence of these complications.…”
Section: Discussionmentioning
confidence: 99%
“…Haeri et al who investigated the prevalence of EBV seropositivity in 64 healthy pregnant women [ 36 ], demonstrated that 22 (35%) women showed EBV reactivation during pregnancy, regardless of maternal age, race, parity, or insurance type [ 36 ]. Moreover, previous reports have clarified that EBV reactivation during pregnancy lead to poor obstetrical outcomes, such as fetal growth restriction [ 37 ], shorter pregnancy duration [ 38 ], and lower birth weight [ 38 ], despite not showing any symptoms. Thus, we recommend transabdominal ultrasound and/or nonstress tests to determine the presence of these complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our results, together with that of previous study18, indicated that prenatal depression was associated with maternal EBV reactivation. In view of the link between EBV reactivation during pregnancy and adverse offspring development234, it is plausible that prenatal psychosocial stress may promote maternal latent EBV reactivation, which increases the risk of fetal exposure to the virus, and contributes to adverse offspring development. However, EBV reactivation during pregnancy was also considered as a non-causal marker of impaired cellmediated immune function, which could contribute to adverse perinatal health outcomes27.…”
Section: Discussionmentioning
confidence: 99%
“…Like other herpes viruses, EBV has the ability to remain latent in the body and becomes reactivated at a later time. It has been reported that maternal EBV reactivation in pregnancy is related to the adverse offspring development including severe symmetrical fetal growth restriction, lower birthweight, and leukemia234.…”
mentioning
confidence: 99%
“…Identification and characteristics of the EBV infection in the placenta has been elusive. A few papers argued that the EBV infection is associated with various pathologic conditions during pregnancy, including depression, preeclampsia, and stillbirth ( 7 8 9 ). These findings are mostly thought to be associated with EBV infection of the B lymphocytes; confirmed by polymerase chain reaction (PCR) or serological tests with blood samples which do not involve histopathological information.…”
Section: Introductionmentioning
confidence: 99%